Monitoring and evaluation data requirement guide - Azzarri, Carlo; Haile, Beliyou (International Institute of Tropical Agriculture, 2017)
Monitoring and Evaluation (M&E) are integral parts of project management and play a crucial role in assessing the efficiency and effectiveness of investments in research and development interventions. Inadequate planning and capacity for timely collection, analysis, and dissemination of data are among the challenges usually faced during the M&E of programs, outputs, and outcomes. This document provides a guideline on M&E data requirements for Africa RISING (hereon after AR) to ease some of these challenges. The successful implementation of the guidelines herein requires a strong collaboration and follow up by the M&E team, AR researchers, chief scientists, and program managers as summarized in Table 1 below. The rest of the guide is organized as follows. Section 1 outlines data needs regarding different types of program beneficiaries and sustainable intensification (SI) innovations. Section 2 discusses Feed the Future indicators data requirements. Notes about the indicators of SI developed by Michigan State University researchers as part of the SI Indicators Framework (SIIF) are in Section 3. Section 4 discusses some guidelines for agronomic and socioeconomic data collection.